Iot based Smart Stickfor Visually Challenged Using Lora - Deborah Roseline P., Santhosh P. K., Philomina Jenifer A., Rajkumar M. G., Vishvanthini G. (International Journal of Advanced Science and Technology, 2020)
This paper presents an idea about dealing with the problems faced by blind people through smart stick .The setup evaluates the  performance of our design in a downlink scenario where the transmitter is embedded on the streetlights is used as receiver, therefore achieving the goal of lighting and communicating simultaneously. To validate the design, simulation of the whole system are  performed. Where simulations of the channel between streetlight show the scope of the reflection in an outdoor environment. We are introducing a smart stick which will assist them in their motion other needed activities. The stick will be detecting nearby obstacles and eventually give a feedback to the person holding it. So thereby, the blind person will get to know about the obstacles around them without any help or guidance of someone else. We also used streetlight to guide them to know his current location. It does not require anyexternal power sources. The MEMS sensor is used for detect the blind people axis changes and messages send to the authorized person using MQTT protocol.